All Cats are Gray in the Dark: Enrichment/Depletion Approaches for Biomarker Discovery on Felis catus Plasma. Issue 20 (8th October 2018) - Carcangiu, Laura; Pisanu, Salvatore; Tore, Silvia; Addis, Maria Filippa; Zini, Eric; Uzzau, Sergio; Pagnozzi, Daniela
Abstract: In veterinary medicine, assay performance is often affected by the lack of species‐specific diagnostic tools. Reliable biomarkers might be identified by investigating biological fluids of the species of interest, but protein sequence databases are often incomplete and human‐specific devices for reducing sample complexity might fail when applied to animal plasma. Here, seven commercial methods based on different capturing agents (anti‐human antibodies, affinity ligands, mixture of antibodies and ligands, and combinatorial peptide ligand libraries) are applied to cat plasma and evaluated in terms of yield, identified proteins/ peptides, and relative abundance by high‐resolution shotgun proteomics and label‐free quantitation. As a result, anti‐human antibody‐based methods are unsatisfactory. Most fail in reducing albumin and immunoglobulins, and some lead to a substantial removal of other highly abundant proteins, probably because of nonspecific interactions. A protein A/dye ligand‐based method is efficient in reducing immunoglobulins, fibrinogen, and apolipoprotein A1 and A2, but not albumin, and protein identifications do not increase. Only peptide ligand libraries flatten the dynamic range, and increased protein identification (59.0%). Albumin and immunoglobulins are successfully depleted (60.7% and 35.9%, respectively). Although further studies will be required for reinforcing our observations, this work can provide a useful guide for cat plasma pretreatment in biomarker discovery studies.